Composite membrane material for oil-water separation as well as preparation method and application of composite membrane material
By combining MgFe-LDH with PVDF membrane and solidifying the load through dopamine chemical crosslinking, MgFe-LDH/pDA/PVDF composite membrane material was prepared, which solved the problem of poor anti-fouling performance of PVDF membrane, and achieved good long-term separation and high throughput of the emulsion.
Patent Information
- Application Number
- CN202510316413.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-18
AI Technical Summary
The existing PVDF membrane materials have poor anti-fouling performance during oil-water separation, resulting in small flux and poor long-term separation performance.
MgFe-LDH/pDA/PVDF composite membrane material was prepared by combining MgFe-LDH as a functional load with the PVDF membrane and achieving solid loading by chemical crosslinking of dopamine.
This composite film material significantly improves the anti-pollution performance, achieves a good long-term separation effect on emulsions formed by different types of oils, and maintains a high flux.
Smart Images

Figure CN119896980A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and in particular relates to a composite membrane material for oil-water separation and a preparation method and application thereof. Background Art
[0002] At present, wastewater generated in the process of oil extraction, processing, transportation, chemical industry, machinery and food processing often contains a large amount of oil substances. Because its density is less than that of water, once oily wastewater enters the receiving water body, an oil film will be formed on the surface, resulting in a decrease in the oxygen content in the water. In the long run, it will cause hypoxia in the water body, causing the death of aquatic organisms and water environment problems. At the same time, oily wastewater is generally potentially carcinogenic, posing a serious threat to human health and water ecological safety. Oily wastewater is mainly divided into three types: floating oil, dissolved oil and emulsified oil. Among them, emulsified oil refers to tiny oil particles (liquid or semi-solid) that exist in a stable state (not floating, not condensing). It must be demulsified and converted into floating oil before it can be separated. Therefore, emulsified oil is also the most difficult type of oil-water emulsion to treat. The main emulsified oil treatment technologies currently include: pressurized air flotation, chemical coagulation, electrochemical method and membrane separation. Among them, pressurized air flotation and chemical coagulation are generally used in combination, with the advantages of mature technology and good treatment effect, but this treatment method occupies a large area and produces a large amount of sludge, which is difficult to handle later. Electrochemical oil removal is highly efficient and can achieve continuous oil-water separation, but the required separation device is complex and consumes a lot of electricity, especially the anode metal is easily corroded and consumed. In contrast, membrane separation technology, as a new modern water treatment technology, has the advantages of small footprint, simple operation, continuous water inlet, low energy consumption, and no waste generation, showing great application potential in the field of oily wastewater treatment.
[0003] The application of membrane separation technology in oil-water separation is mainly ultrafiltration (UF). PVDF membrane, as a membrane material with a high degree of compatibility with UF, has become one of the most valuable organic polymer membrane materials for research due to its good chemical stability, high mechanical strength, corrosion resistance, radiation resistance, and UV resistance. It is widely used in the field of oil-water separation. However, since emulsified oil droplets often adhere to the membrane surface or completely fill the membrane pores during the separation process, PVDF membranes are easily contaminated by oil substances, resulting in a sharp drop in flux during the separation of oil-water emulsions, and also showing poor long-term separation performance. This not only fails to achieve effective purification of oily wastewater, but may also increase the risk of effluent pollution. Given that PVDF membranes are affected by emulsified oil droplets in oil-water separation applications, improving the ability to resist oil pollution is an important way to solve the problem of PVDF membrane pollution.
[0004] Therefore, it is crucial to develop new PVDF membrane materials with special surface properties, and it is necessary to design a new composite membrane material for oil-water separation and its preparation method and application. Summary of the invention
[0005] The purpose of the present invention is to provide a composite membrane material for oil-water separation and a preparation method and application thereof, so as to solve the problems mentioned in the background technology, such as low flux and poor long-term separation performance caused by poor anti-fouling performance of current PVDF membrane materials.
[0006] To achieve the above-mentioned purpose, the present invention provides a method for preparing a composite membrane material for oil-water separation, wherein PVDF is used as a base membrane and MgFe-LDH is used as a functional load, and the two are immobilized by dopamine chemical cross-linking to obtain a MgFe-LDH / pDA / PVDF composite membrane material.
[0007] In a specific implementation, the method comprises the following steps:
[0008] S1. Mix N,N'-dimethylformamide (DMF), PVDF and polyvinylpyrrolidone (PVP), heat and stir to react for a period of time, and then age to remove bubbles to form a casting solution. Pour the casting solution on a dry and flat glass plate and spread it evenly. Soak the glass plate in pure water to form a PVDF membrane.
[0009] S2, soaking the PVDF membrane obtained in step S1 in an ethanol solution for a period of time, then immersing it in a Tris-HCl buffer solution, adjusting the pH of the buffer solution, adding dopamine, and self-polymerizing under certain conditions to obtain a pDA / PVDF membrane;
[0010] S3. Dissolve the solid mixture of magnesium nitrate, ferric nitrate and urea in ultrapure water to prepare a mixed solution, immerse the pDA / PVDF membrane obtained in step S2 in the mixed solution, transfer it to a high-pressure reactor, and react under certain conditions to obtain a MgFe-LDH / pDA / PVDF composite membrane material.
[0011] In a specific embodiment, in step S1, the molar ratio of DMF, PVDF and PVP is 60-80:10-20:1-10.
[0012] In a specific embodiment, the heating and stirring reaction temperature of step S1 is 40-90° C., the stirring time is 4-24 hours, and the reaction device is a magnetic stirrer.
[0013] In a specific embodiment, in step S2, the pH value of the Tris-HCl buffer solution is adjusted to 7.5-9; the concentration of dopamine (DA) is 5-40 mmol.
[0014] In a specific embodiment, in step S2, the self-polymerization is carried out by shaking, the reaction conditions are shaking at 30-50° C. for 4-20 hours, and the reaction apparatus is a shaker.
[0015] In a specific embodiment, in step S3, the molar ratio of magnesium nitrate, ferric nitrate and urea is 1.5-6:0.5-3:1-9; after the mixed solution is ultrasonicated for 5-60 minutes, the pH is adjusted to 4-11.
[0016] In a specific embodiment, the reaction temperature in step 3 is 60-180° C., and the reaction time is 6-36 hours.
[0017] The present invention also provides a composite membrane material for oil-water separation, wherein the composite membrane material is prepared by the preparation method as described above.
[0018] The present invention also provides an application of a composite membrane material prepared by the preparation method as described above, which is applied to the oil-water separation of an emulsion, wherein the emulsion exists in a stable state, i.e., tiny oil particles, liquid or semi-solid that do not float or condense, and whose particle size is 0.5 to 25 μm.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The MgFe-LDH / pDA / PVDF composite membrane material prepared by the present invention effectively solves the problem of poor membrane flux and separation performance caused by poor anti-pollution performance of conventional PVDF membranes, and provides effective reference and experience for the development and implementation of emulsion separation and purification technology based on composite membrane materials.
[0021] The MgFe-LDH / pDA / PVDF composite membrane material of the present invention exhibits good long-term separation effect on emulsions formed by different types of oils.
[0022] In addition to the above-described objects, features and advantages, the present invention has other objects, features and advantages. The present invention is further described in detail below. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The drawings constituting a part of this application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0024] Figure 1 It is a comparison chart of the antifouling performance of the PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane in the present invention;
[0025] Figure 2 is a SEM image of the PVDF membrane of the present invention;
[0026] Figure 3 is a SEM image of the pDA / PVDF membrane of the present invention;
[0027] Figure 4 is a SEM image of the MgFe-LDH / pDA / PVDF composite membrane of the present invention;
[0028] Figure 5 is the WCA diagram of the PVDF membrane in the present invention;
[0029] Figure 6 is the WCA diagram of the pDA / PVDF membrane in the present invention;
[0030] Figure 7 is the WCA diagram of the MgFe-LDH / pDA / PVDF composite membrane of the present invention;
[0031] Figure 8 is the UOCA diagram of the PVDF membrane in the present invention;
[0032] Fig. 9 is the UOCA diagram of the pDA / PVDF membrane of the present invention;
[0033] Fig.10 is the UOCA diagram of the MgFe-LDH / pDA / PVDF composite membrane of the present invention;
[0034] Fig.11 This is a diagram showing the cyclic separation effect of the PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane on the engine oil / water emulsion;
[0035] Fig.12 This is a diagram showing the cyclic separation effect of kerosene / water emulsion by the PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane of the present invention;
[0036] Fig.13 This is a diagram showing the cyclic separation effect of the PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane on the vegetable oil / water emulsion;
[0037] Fig.14 It is a diagram showing the cyclic separation effect of the PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane on n-heptane / water emulsion in the present invention;
[0038] Fig.15 This is a diagram showing the cyclic separation effect of the PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane on petroleum ether / water emulsion;
[0039] Fig.16This is a graph showing the long-term separation of the engine oil / water emulsion by the MgFe-LDH / pDA / PVDF composite membrane of the present invention;
[0040] Fig.17 This is a graph showing the long-term separation of kerosene / water emulsion by the MgFe-LDH / pDA / PVDF composite membrane of the present invention;
[0041] Fig.18 This is a graph showing the long-term separation of vegetable oil / water emulsion by the MgFe-LDH / pDA / PVDF composite membrane of the present invention;
[0042] Fig.19 This is a long-term separation performance diagram of the MgFe-LDH / pDA / PVDF composite membrane of the present invention for n-heptane / water emulsion;
[0043] Fig. 20 This is a diagram showing the long-term separation performance of the MgFe-LDH / pDA / PVDF composite membrane of the present invention on petroleum ether / water emulsion. DETAILED DESCRIPTION
[0044] The embodiments of the present invention are described in detail below. The specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0045] The invention discloses a method for preparing a composite membrane material for oil-water separation, which uses PVDF as a base membrane and MgFe-LDH as a functional load, and the two are immobilized by dopamine chemical cross-linking to obtain a MgFe-LDH / pDA / PVDF composite membrane material.
[0046] The specific steps include:
[0047] S1. Mix N,N'-dimethylformamide (DMF), PVDF and polyvinylpyrrolidone (PVP), wherein the molar ratio of DMF, PVDF and PVP is 60-80:10-20:1-10; heat and stir to react, wherein the heating and stirring reaction temperature is 40-90°C, the stirring time is 4-24 hours, and the reaction device is a magnetic stirrer; after aging and removing bubbles, a casting liquid is formed, and the casting liquid is poured on a dry and flat glass plate and evenly applied, and the glass plate is immersed in pure water to form a PVDF membrane;
[0048] S2, soaking the PVDF membrane obtained in step S1 in an ethanol solution for a period of time, and then immersing it in a Tris-HCl buffer solution, adjusting the pH value of the Tris-HCl buffer solution to 7.5-9; adding dopamine, the concentration of dopamine (DA) is 5-40mmol, and self-polymerizing by shaking, the reaction conditions are shaking at 30-50°C for 4-20h, and the reaction device is a shaker, so as to obtain a pDA / PVDF membrane;
[0049] S3, dissolving a solid mixture of magnesium nitrate, ferric nitrate and urea in ultrapure water to prepare a mixed solution, wherein the molar ratio of magnesium nitrate, ferric nitrate and urea is 1.5-6:0.5-3:1-9; after ultrasonicating the mixed solution for 5-60 minutes, adjusting the pH value to 4-11; immersing the pDA / PVDF membrane obtained in step S2 in the mixed solution, transferring it to a high-pressure reactor, reacting at a reaction temperature of 60-180°C and a reaction time of 6-36 hours, thereby obtaining a MgFe-LDH / pDA / PVDF composite membrane material.
[0050] The present invention also provides a composite membrane material for oil-water separation, wherein the composite membrane material is prepared by the preparation method as described above.
[0051] The present invention also provides an application of a composite membrane material prepared by the preparation method as described above, which is applied to the oil-water separation of an emulsion, wherein the emulsion exists in a stable state, i.e., tiny oil particles, liquid or semi-solid that do not float or condense, and whose particle size is 0.5 to 25 μm.
[0052] Example 1
[0053] This embodiment is a method for preparing a MgFe-LDH / pDA / PVDF composite membrane, comprising the following steps:
[0054] (1) N,N'-dimethylformamide (DMF), PVDF, and polyvinylpyrrolidone (PVP) were mixed in a molar ratio of 89:10:1 and heated and stirred at 80°C for 24 hours. After aging to remove bubbles, the casting solution was poured onto a dry and flat glass plate and spread evenly. The glass plate was immersed in pure water to generate a PVDF membrane.
[0055] (2) The PVDF membrane obtained in step (1) was immersed in an ethanol solution, and then immersed in 10 mL of Tris-HCl (10 mM) buffer solution. After adjusting the pH of the buffer solution to 9, 10 mM dopamine was added, and dopamine (DA) was self-polymerized under oscillation for 4 h to obtain a pDA / PVDF membrane.
[0056] (3) Dissolve Mg(NO3)2·6H2O, Fe(NO3)3·9H2O and urea in ultrapure water at a molar ratio of 1.5:1:2, adjust the pH of the solution to 5, soak the pDA / PVDF membrane obtained in step (2) in the solution, transfer to a high-pressure reactor, and react at 60°C for 6 hours to obtain a MgFe-LDH / pDA / PVDF composite membrane material.
[0057] Example 2
[0058] The contact angles of PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were tested. The water contact angles (WCA) were 137.6°, 86.3°, and 0°, respectively. The underwater oil contact angles (UOCA) were 22.3°, 110.2°, and 154.6°, respectively. Figures 5 to 10 As shown. The water contact angle and underwater oil contact angle are used to represent the hydrophilicity and hydrophobicity of the membrane. The results show that with the in-situ loading of MgFe-LDH, the hydrophilicity of the membrane becomes better and better, which is conducive to the application of emulsified oil type oil-water separation.
[0059] Example 3
[0060] Prepare a BSA solution with a concentration of 0.5 g / L, and place the PVDF membrane, pDA / PVDF, and MgFe-LDH / pDA / PVDF composite membrane in a low-pressure flat membrane filtration device, with an effective membrane area of 4 cm 2 The water flux and BSA antifouling experiments were carried out under constant transmembrane pressure (0.1 MPa). The experimental results showed that the initial water flux of PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were 2090 L·m -2 ·h -1 bar -1 、910L·m -2 ·h -1 bar -1 、680L·m -2 ·h -1 bar -1 After a single cycle, the flux recovery rates of PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were 51%, 63%, and 91%, respectively. Figure 1 Compared with PVDF membrane and pDA / PVDF membrane, although the flux of MgFe-LDH / pDA / PVDF composite membrane is lower, the flux recovery rate is higher, which proves that MgFe-LDH / pDA / PVDF composite membrane has better anti-fouling performance.
[0061] Example 4
[0062] The engine oil and water were mixed in a ratio of 1:49 and magnetically stirred for 12 hours to form an emulsion. The PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were placed in an ultrafiltration cup for a cyclic membrane test. The experimental results showed that after 8 cycles, the separation efficiency of the PVDF membrane and pDA / PVDF membrane for the engine oil / water emulsion was less than 20%, while the separation efficiency of the MgFe-LDH / pDA / PVDF composite membrane remained above 90%. Fig.11 The results show that the MgFe-LDH / pDA / PVDF composite membrane has a good separation effect on the oil / water mixed emulsion and can be used for multiple cycles.
[0063] Example 5
[0064] Kerosene and water were mixed in a ratio of 1:49 and magnetically stirred for 12 hours to form an emulsion. PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were placed in an ultrafiltration cup for a cyclic membrane test. The experimental results showed that after 8 cycles, the separation efficiency of PVDF membrane and pDA / PVDF membrane for kerosene / water emulsion was less than 20%, while the separation efficiency of MgFe-LDH / pDA / PVDF composite membrane remained above 90%. Fig.12 The results show that the MgFe-LDH / pDA / PVDF composite membrane has a good separation effect on the kerosene / water mixed emulsion and can be used for multiple cycles.
[0065] Example 6
[0066] Vegetable oil and water were mixed in a ratio of 1:49 and magnetically stirred for 12 hours to form an emulsion. PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were placed in an ultrafiltration cup for a cyclic membrane experiment. The experimental results showed that after 8 cycles, the separation efficiency of PVDF membrane and pDA / PVDF membrane for vegetable oil / water emulsion was less than 20%, while the separation efficiency of MgFe-LDH / pDA / PVDF composite membrane remained above 90%. Fig.13 The results show that the MgFe-LDH / pDA / PVDF composite membrane has a good separation effect on the vegetable oil / water mixed emulsion and can be used for multiple cycles.
[0067] Example 7
[0068] n-heptane and water were mixed in a ratio of 1:49 and magnetically stirred for 12 hours to form an emulsion. PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were placed in an ultrafiltration cup for a cyclic membrane experiment. The experimental results showed that after 8 cycles, the separation efficiency of PVDF membrane and pDA / PVDF membrane for n-heptane / water mixed emulsion was less than 20%, while the separation efficiency of MgFe-LDH / pDA / PVDF composite membrane remained above 90%. Fig.14 The results show that the MgFe-LDH / pDA / PVDF composite membrane has a good separation effect on the n-heptane / water mixed emulsion and can be used for multiple cycles.
[0069] Example 8
[0070] Petroleum ether and water were mixed in a ratio of 1:49 and magnetically stirred for 12 hours to form an emulsion. PVDF membrane, pDA / PVDF membrane, and MgFe-LDH / pDA / PVDF composite membrane were placed in an ultrafiltration cup for a cyclic membrane experiment. The experimental results showed that after 8 cycles, the separation efficiency of PVDF membrane and pDA / PVDF membrane for the emulsion of petroleum ether / water mixture was less than 20%, while the separation efficiency of MgFe-LDH / pDA / PVDF composite membrane remained above 90%. Fig.15 The results show that the MgFe-LDH / pDA / PVDF composite membrane has a good separation effect on the petroleum ether / water mixed emulsion and can be recycled for multiple times.
[0071] Example 9
[0072] Emulsions of motor oil / water, kerosene / water, vegetable oil / water, n-heptane / water and petroleum ether / water were prepared, and the MgFe-LDH / pDA / PVDF composite membrane was placed in a low-pressure flat membrane filtration device with an effective membrane area of 4 cm2. The oil-water separation experiment was carried out for 1000 min under a constant transmembrane pressure (0.1 MPa). The experimental results show that after 1000 min of separation experiment, the separation efficiency of the MgFe-LDH / pDA / PVDF composite membrane for the emulsions of five different types of oils has been stably maintained at more than 90%, and the flux has been maintained at more than 50% of the initial emulsion flux, showing good long-term separation performance for emulsions of various types of oils, such as Figures 16-20 shown.
[0073] The MgFe-LDH / pDA / PVDF composite membrane material of the present invention greatly alleviates the membrane contamination of the traditional PVDF membrane material during oil-water separation, can achieve long-term separation of emulsions of various types of oils, and exhibits excellent oil-water separation flux.
[0074] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple deductions and substitutions can be made without departing from the concept of the present invention, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing a composite membrane material for oil-water separation, characterized in that: Using PVDF as the base membrane and MgFe-LDH as the functional load, the two were immobilized through dopamine chemical cross-linking to obtain MgFe-LDH / pDA / PVDF composite membrane material.
2. The method for preparing a composite membrane material for oil-water separation according to claim 1, characterized in that: The specific steps include: S1. Mix N,N'-dimethylformamide (DMF), PVDF and polyvinylpyrrolidone (PVP), heat and stir to react for a period of time, and then age to remove bubbles to form a casting solution. Pour the casting solution on a dry and flat glass plate and spread it evenly. Soak the glass plate in pure water to form a PVDF membrane. S2, soaking the PVDF membrane obtained in step S1 in an ethanol solution for a period of time, then immersing it in a Tris-HCl buffer solution, adjusting the pH of the buffer solution, adding dopamine, and self-polymerizing under certain conditions to obtain a pDA / PVDF membrane; S3. Dissolve the solid mixture of magnesium nitrate, ferric nitrate and urea in ultrapure water to prepare a mixed solution, immerse the pDA / PVDF membrane obtained in step S2 in the mixed solution, transfer it to a high-pressure reactor, and react under certain conditions to obtain a MgFe-LDH / pDA / PVDF composite membrane material.
3. The method for preparing a composite membrane material for oil-water separation according to claim 2, characterized in that: In the step S1, the molar ratio of DMF, PVDF and PVP is 60-80:10-20:1-10.
4. The method for preparing a composite membrane material for oil-water separation according to claim 2, characterized in that: The heating and stirring reaction temperature of step S1 is 40-90° C., the stirring time is 4-24 hours, and the reaction device is a magnetic stirrer.
5. The method for preparing a composite membrane material for oil-water separation according to claim 2, characterized in that: In step S2, the pH value of the Tris-HCl buffer solution is adjusted to 7.5-9; the concentration of dopamine (DA) is 5-40 mmol.
6. The method for preparing a composite membrane material for oil-water separation according to claim 2, characterized in that: In the step S2, the self-polymerization is carried out by shaking, the reaction conditions are shaking at 30-50° C. for 4-20 hours, and the reaction device is a shaker.
7. The method for preparing a composite membrane material for oil-water separation according to claim 1, characterized in that: In step S3, the molar ratio of magnesium nitrate, ferric nitrate and urea is 1.5-6:0.5-3:1-9; after the mixed solution is ultrasonicated for 5-60 minutes, the pH value is adjusted to 4-11.
8. The method for preparing a composite membrane material for oil-water separation according to claim 1, characterized in that: In step 3, the reaction temperature is 60-180° C., and the reaction time is 6-36 hours.
9. A composite membrane material for oil-water separation, characterized in that: The composite membrane material is prepared by the preparation method described in any one of claims 1 to 8.
10. An application of a composite membrane material prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The invention is applied in the separation of oil and water in emulsion, wherein the emulsion exists in a stable state, that is, tiny oil particles, liquid or semi-solid which neither floats nor condenses, and the particle size thereof is 0.5 to 25 μm.
Citation Information
Patent Citations
Modified polyvinylidene fluoride oil-water separation membrane and application thereof in sewage treatment
CN114130226A
Oil-water separation membrane as well as preparation method and application thereof
CN114988519A
Iron-manganese hydrotalcite composite membrane and application thereof in removal of quinolone antibiotics
CN116603399A
PDA / TA / FeOOH-PVDF self-cleaning membrane as well as preparation method and application thereof
CN119368008A
Membrane type oil-water separator, membrane washing method, washing system using membrane type oil-water separator, and oil-water separating system of water-soluble coolant liquid
JP2007301544A